Variational collocation for systems of coupled anharmonic oscillators - Amore, Paolo (2010)
By means of a collocation approach based on little sinc functions (LSF), we obtain accurate eigenvalues and eigenfunctions of the stationary Schrödinger equation for systems of coupled oscillators. Adjustable parameters introduced by means of scaling and rotation of the coordinates improve the rate of convergence of the approach. A careful comparison with the results published earlier by other authors shows the advantages of the present approach.